Behind Productivity: How Workload Affects Employee Well-being? - Rubiyanti Rubiyanti; Ros Patriani Dewi (Psikostudia : Jurnal Psikologi, 2026)
Employee well-being is an essential factor that determines organizational stability and productivity, particularly in the manufacturing sector where work demands are relatively high. An imbalance in workload may reduce employees’ physical and psychological conditions, thereby affecting their performance. This study aims to examine the effect of workload on employee well-being at CV. X, a tile manufacturing company in Yogyakarta. The research employed a quantitative approach using the NASA-TLX workload scale and the Employee Well-Being Scale. The study involved 65 employees selected through purposive sampling. Data analysis was conducted using simple regression. The results indicate a significant negative effect of workload on employee well-being, with a regression coefficient of -0.363 (p < 0.05). The R Square value of 0.218 shows that workload contributes 21.8% to the variation in employee well-being. These findings confirm that higher perceived workload is associated with lower levels of employee well-being. The implications highlight the importance of effective workload management, equitable task distribution, and supportive organizational policies to maintain employees’ physical and psychological well-being, thus ensuring sustained productivity and operational continuity within the company.Kesejahteraan karyawan merupakan aspek penting yang menentukan stabilitas dan produktivitas perusahaan, terutama pada sektor manufaktur yang memiliki tuntutan kerja tinggi. Beban kerja yang tidak seimbang dapat menurunkan kondisi fisik maupun psikologis karyawan sehingga berdampak pada performa kerja. Penelitian ini bertujuan untuk menganalisis pengaruh beban kerja terhadap kesejahteraan karyawan pada CV. X, perusahaan manufaktur ubin tegel di Yogyakarta. Penelitian menggunakan pendekatan kuantitatif dengan instrumen skala beban kerja (NASA-TLX) dan Employee Well-Being Scale. Subjek penelitian berjumlah 65 karyawan yang dipilih melalui teknik purposive sampling. Analisis data dilakukan menggunakan regresi sederhana. Hasil penelitian menunjukkan adanya pengaruh negatif yang signifikan antara beban kerja dan kesejahteraan karyawan dengan koefisien regresi sebesar -0,363 (p < 0,05). Nilai R Square sebesar 0,218 menunjukkan bahwa beban kerja memberikan kontribusi sebesar 21,8% terhadap variasi kesejahteraan karyawan. Temuan ini menegaskan bahwa semakin tinggi beban kerja yang dirasakan, semakin rendah tingkat kesejahteraan karyawan. Implikasi penelitian ini menekankan pentingnya pengelolaan beban kerja yang efektif, pembagian tugas yang adil, serta kebijakan organisasi yang mendukung kesejahteraan fisik dan psikologis karyawan guna menjaga produktivitas serta keberlanjutan operasional perusahaan.